Kingdee in 2011 : stranding or dormancy - McFarlan, F. Warren (Franklin Warren); Zhang, Jin, 1967-; Li, Xiaohui ([London] : SAGE, 2016)
On February 2, 2012, Kingdee International announced that Richard Feng had resigned as Kingdee's executive director and president and CEO of Kingdee Software (China) Company Ltd., a wholly-owned subsidiary of Kingdee, due to family committments and other personal reasons, and would now be appointed as strategy consultant. At that time, Richard had served as Kingdee's president for one year. This case study examines this topic.
Originally Published in: McFarlan, F. W., Zhang, J., & Li, X. (2012). Kingdee in 2011: Standing or Dormancy? 6-312-352. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Kingdee (Firm); Strategic planning -- China -- Case studies